Screening in the credit market when the collateral value is stochastic - Juha-Pekka Niinimäki (Bank of Finland, 2009)
This theoretical paper explores screening with loan collateral when both the collateral value and the probability of project success fluctuate. Some model versions challenge the classic findings of Bester (1985) by showing that high-risk borrowers may in such case be more willing to pledge collateral than low-risk borrowers. Abundant collateral then would not signal low risk. The results may help explain the mixed empirical findings on the role of collateral. The paper also extends the analysis of the topical subprime crises and risky real estate collateral
URN:NBN:fi:bof-20140807582
Keywords: 330